Analysis of the Impact of Executive Functions on Reading Comprehension in Schoolchildren with Dyslexia - Agost Carreño, María Cecilia (2026)
Objective. The aim of this study was to analyze whether executive functions (working memory, inhibition and flexibility) account for differences in reading comprehension between strong and weak readers with dyslexia. The analysis was done while controlling the level of reading access and considering verbal comprehension, vocabulary, and IQ. Furthermore, the study sought to identify which of these variables were the best predictors of reading comprehension in this population. Method. Fifty-one patients diagnosed with dyslexia (34 boys and 17 girls; aged between 9.9 and 13 years) who were in between 5th to 7th grade of school and attending a clinic for the detection of learning disorders were assessed. Based on a text comprehension test, two groups were formed: good and poor comprehenders. Results. The results showed that differences in executive functions did not explain the variability in reading comprehension in this group. Although an initial analysis highlighted IQ as the main explanatory variable, stepwise hierarchical regression analyses identified vocabulary and working memory as the main predictors of good reading comprehension. These findings are discussed within the framework of the cognitive models of reading.